Effects of missense mutations on protein function in human disease: tumor suppressor p53 and the AAA+ ATPase CLPB - Thevarajan, Indhujah (Kansas State University, 2020)
The human genome consists of more than three billion base pairs, and an alteration in one base pair may lead to a disease condition. However, not all mutations have harmful effects and some mutations are beneficial to the organism. Mutations are important in evolution and allow a natural selection to occur. When the DNA sequence in a protein coding region is altered by point mutation, it may produce a partially or completely non-functional protein. In my study, we selected disease-associated missense mutations in two different human proteins: the p53 protein and the AAA+ ATPase CLPB. The goal of my research was to explore the effects of these missense mutations on protein function in disease. Tumor suppressor p53 is a frequently mutated gene in human cancers. Since previous studies mainly focused on mutations in the DNA binding domain (DBD) of p53 protein, very little is known about the structural and functional consequences of the cancer-associated mutations in the p53 transactivation domain (TAD). The level and activity of p53 are regulated by interactions of TAD with the negative regulator HDM2 and the general transcriptional co-activator CBP. Four cancer-associated mutations in p53-TAD were selected for this study and the interaction with its binding partners, HDM2 and CBP, were investigated using in vitro protein-binding assays utilizing Biolayer Interferometry (BLI). I found that the cancer-associated mutations can significantly perturb the balance of p53’s interactions with the key activator (CBP) and the degradation regulator (HDM2). Human caseinolytic peptidase B protein homolog (CLPB)/suppressor of potassium transport defect 3 (SKD3) belongs to the AAA+ family of ATPases associated with different activities. Mutations in the human CLPB gene cause 3-methylglutaconic aciduria type VII with cataracts, neurologic involvement, and neutropenia (MEGCANN), a rare autosomal recessive genetic disease affecting children. The function of CLPB is unknown and its relation to the well-studied microbial disaggregase ClpB/Hsp104 has been controversial. The clinical manifestations of the mutations are currently challenging to explain due to the lack of understanding of the biological function of CLPB. To begin closing that gap in knowledge, I investigated the endogenous CLPB in mammalian cells and exogenously overexpressed CLPB. I found that endogenous human CLPB is found predominantly in the mitochondrial intermembrane space. I demonstrated that the selected disease-associated variants of human CLPB showed different levels of expression from WT CLPB. Overexpressed CLPB, while properly trafficked to the mitochondria, appeared to form large clusters/aggregates that were poorly extractable with non-ionic detergents and were readily visualized by immunofluorescence microscopy. Importantly, endogenous CLPB formed high molecular weight protein complexes in an ATP-dependent manner, indicating that ATP binding induces a conformational change in CLPB and controls its ability to self-associate or form complexes with other proteins. Collectively, these findings should inform future studies on the effect of pathogenic mutations on CLPB structure and function and on the mechanism of CLPB action in human cells.
Keywords: Tumor suppressor p53; Human CLPB; Mutations; Disease; Intrinsically disordered protein; Mitochondria